Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Matematika menggunakan Model Make a Match dengan Berbantuan Media Flip Chart Kelas IV SDN-2 Kasongan Baru Tahun Pelajaran 2016/2017: Efforts to Improve Student Learning Outcomes in Mathematics Subjects using the Model Make a Match with Assisted Media Flip Chart Class IV SDN-2 Kasongan New Academic Year 2016/2017 - Azizah Febriani; Dedy Setyawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to find out: (1) Learner Learning Activities, (2) Knowing the Improvement of Mathematics Learning Outcomes After Using the Make a Match Model of media assistance Flip Chart In the Summarization Material Split in the fourth class of Kasongan Baru SDN-2. This study is classroom action research (PTK). The subjects of this study were fourth-grade students of the New Kasongan Elementary School-2 in the 2016/2017 Academic Year consisting of 12 students. Analysis of the data used in this study is quantitative data and qualitative data. Based on the research obtained: (1) Learning activities of fourth-grade students of Kasongan New SDN-2 after using the model make a Match media assistance Flip Chart in the first cycle average score of 3.45 becomes good. From the observations that have been made it can be concluded that the learning activities of students fall into the excellent category. (2) There is an increase in learning outcomes of Grade IV students of SDN-2 Kasongan Baru using the make a Match-assisted media model Flip Chart experienced a boost from the initial data of an average of 44 and classical completeness of 33%. The average value in cycle I 76 and integrity in traditional 100%